The correct stems of family-group names citing Ortalis Merrem, 1786, as type genus (Aves: Cracidae) - David, Normand (Zootaxa, 2014)
Donegan (2012) proposed the family-group name "Ortalidaini n. tribe" for the chachalaca group in the avian family Cracidae (guans), and designated "Ortalis (or Ortalida)" [sic] Merrem, 1786, as the type genus. For reasons given below, the name "Ortalidaini" is showed to be misformed according to the International Code of Zoological Nomenclature (ICZN 1999), hereinafter the Code, and the correct stems of family-group names using Ortalis Merrem, 1786, as type genus are presented.